The influence of educational service quality on parent and student satisfaction in Private High School X, Bandung City - Slamet, Yehezkiel Bobby; Saputra, Bobby Wiryawan (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to determine the influence of the quality of educational services on the satisfaction of students and parents of students at private high school X, Bandung City. This research was conducted in West Java Province, especially at Senior High School (SMA) "X" Bandung city which is a private school with a national level plus and accredited A. The population of this research is all students in grades 10, 11, and 12 totaling 68 people and their parents, namely 34 people. From the results of the research data processing, it was found that the dimension that had the lowest average value compared to other dimensions both from the responses of parents and students was tangibles. The average score of the students' responses was 3.06 with the good category, while the parents' responses had a value of 3.07 with the bad category. The quality of education services has a positive and significant influence on students' satisfaction with the total influence of 97.9%.